Semmelweis to Szent Rókus - Galef, Daniel (Ars Medica, 2018)
This is a sonnet modeled after the persona poems composed by Lee-Hamilton, written from the point of view of historical characters. The subject is nineteenth-century Hungarian obstetrician Ignaz Semmelweis, and he addresses “Szent Rókus,” the name of both the small hospital he was exiled to in Budapest following his expulsion from Vienna as well as the Hungarian name of Saint Roch, patron of surgeons, gravediggers, and the falsely accused. Semmelweis himself might well be described as falsely accused, as it was the dismissal of his warnings of “cadaverous particles” (admittedly with no real evidence or proposed mechanism) that led to Semmelweis's fall from grace and ultimate involuntary commitment and death. Despite all, he remains one of the earliest proponents of what would eventually become germ theory and the hygiene reforms he instituted in the Vienna General Hospital resulted in a 90% reduction in mortality rate from puerperal fever (postpartum infections).